Pengaruh Logic Exercises Terhadap Disorientasi Moral Jugdment Mahasiswa: Studi Kasus Terorisme - Selly Rahmawati (Universitas PGRI Kanjuruhan Malang, 2018)
The existence of the phenomenon of Indonesian citizens who joined ISIS, the number of teens who become